THE COMPARISON OF PQRST (PREVIEW, QUESTION, READ, STATE, TEST) AND QAR (QUESTION-ANSWER RELATIONSHIP) TECHNIQUES ON STUDENTS WITH DIFFERENT INTEREST ON THEIR READING COMPREHENSION ON PROCEDURE TEXTS AT GRADE VII OF SMPN 2 PADANG - Prih Febtiningsih (Faculty of Teacher Training and Education, 2019)
This research was aimed at knowing whether: 1) The students taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique; 2) The students with high interest taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique; 3) The students with low interest taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique at grade VII of SMPN 2 Padang; 4) Is there any interaction between PQRST and QAR techniques with students’ interest toward reading comprehension of procedure texts? The background of doing this research was that the students got difficulties in comprehending texts namely getting problem in finding accurate information from the texts. Besides, they also had difficulty in remembering the vocabularies that have been learned to the mind. These phenomena were caused by the students’ low capability in memorizing the vocabularies got from the text and the inappropriate teaching reading techniques applied by the teachers so that these made the students’ score and interest on reading comprehension low. In this case, PQRST and QAR techniques could be applied in teaching to help the students comprehend the texts. This research was quasi-experimental research. The population of this research was the students of grade VII of SMPN 2 Padang consisting 184 students spreading in six classes. The sample of this research was taken by using intact group sampling because the students had been grouped into their classes together and taught with the same curriculum and materials, namely 30 students at experimental group (class VII.4) and 30 students as control group (class VII.1). The data of the research were collected through test (pretest and posttest), and questionnaire, and then analyzed using Chi-Square test for normality data testing, variance test for homogeneity data testing and t-test for hypothesis testing. The result of this research showed that: 1) The students taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique; 2) The students with high interest taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique; 3) The students with low interest taught by PQRST technique have significantly higher reading comprehension on procedure text than those who are taught by QAR technique at grade VII of SMPN 2 Padang; 4) There is an interaction between PQRST and QAR techniques with students’ interest toward reading comprehension of procedure texts. Keywords: PQRST, QAR, procedure texts, reading comprehension, different interest